A Case Study of Teachers' Corrective Feedback: Do We Do It Right - Sabariah Abd Rahim; Tengku Sepora Tengku Mahadi (2020)
Effective writing skills are essential for second language university-level students to achieve. To assist these students, writing teachers provide methods to improve their skills in writing, and one of the methods is corrective feedback. Despite applying corrective feedback, L2 university-level students still face challenges in developing their writing skills, especially the skill to produce linguistically accurate writing. Corrective feedback is a form of feedback that is commonly employed pedagogically in writing class. Though, it is unsure whether or not the students are benefited from this method. Therefore, this study aims to elicit second language university-level students’ opinion of teachers’ corrective feedback. Six second language university-level students were interviewed in this study. A qualitative case study research interview was employed in the study, and content analysis method was used to analyze the data. The findings show that students need corrective feedback to improve their writing accuracy. Nevertheless, teachers’ lack of effort in explaining the corrective feedback has resulted in students’ lack of understanding of the corrections made. This affects their writing accuracy. Teachers need to facilitate the feedback to enable the students to respond effectively to the errors presented in their writing. This study is pertinent in providing insights to the teachers for applying an effective strategy to enhance the effectiveness of corrective feedback in an ESL writing class.